High-damping TiZr-based high-entropy alloy with wide temperature range high strength and plasticity and preparation method thereof
Patent Information
- Application Number
- CN202410354165.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-27
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2044-03-27
AI Technical Summary
例如TiZrMoNbTa合金的屈服强度高达σYS=1380MPa,但是由于该合金中存在富Mo/Nb/Ta的高熔点的BCC1相和富Ti/Zr的低熔点的BCC2相,其压缩塑性仅为δ=4.6%
[0019]本发明是根据我们自行发展的团簇成分式方法设计出了一种兼具宽温域高强塑性的高阻尼TiZr基高熵合金,结合高熵合金化实现了元素间的合理配比,确保了BCC结构的稳定性。通过O原子的间隙固溶,不仅促进了变形过程中位错交滑移的产生提高了合金的强塑性,并且合金产生明显的Snoek型弛豫效应使其具有高的阻尼性能。同时高熵合金化带来的晶格畸变效应,提高了间隙O原子的跃迁势垒,其间隙原子弛豫激活能更大,因此提高了阻尼峰温以及有效峰宽。另外,Snoek型阻尼合金的热稳定性更高,提高了合金的服役寿命。该高阻尼TiZr基高熵合金以TiO2粉末作为O的添加剂,制备工艺简单,材料成本大幅降低。
Smart Images

Figure CN118007004B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of damping alloy materials, and relates to a high-damping TiZr-based high-entropy alloy with wide temperature range, high strength and plasticity, and its preparation method. This alloy, through high-entropy alloying and interstitial solid solution of O, produces a significant Snoek-type relaxation effect, giving it high damping performance and high stability. Furthermore, the lattice distortion effect brought about by high-entropy alloying improves the damping peak temperature and effective peak width, making the alloy a promising material for integrated structural and functional damping structures used in high-temperature service environments. Background Technology
[0002] With the rapid development of modern industry, civilian and military fields such as transportation, shipbuilding, and aerospace require precision instruments and other mechanical equipment to have higher accuracy and longer service life during operation. However, these high-power devices inevitably suffer from vibration and noise during service, leading to a reduction in their accuracy and lifespan. Therefore, damping alloys for vibration reduction and noise reduction have received attention and developed rapidly in recent years. Damping alloys can reduce mechanical vibration energy (damping) by relying on internal structural defects (dislocations, twins, point defects, etc.), converting mechanical vibration into heat dissipation, while also possessing certain mechanical properties. The damping performance of damping alloys originates from structural defects present within the alloy itself and generated during processing, preparation, and subsequent heat treatment. Furthermore, the damping magnitude is affected by external factors such as temperature, frequency, and strain amplitude. Under alternating stress, damping alloys often exhibit a phenomenon where strain lags behind stress, meaning there is a phase difference between the two. and The higher the value, the better the damping performance of the alloy. Alloys exhibiting high damping properties are called high-damping alloys. Based on the different damping mechanisms within the alloy, damping alloys can be classified into Snoek-type point defect damping alloys (Ti-Nb alloys), dislocation damping alloys (Mg-Zr alloys, Al-Zn alloys), twinned damping alloys (Mn-Cu alloys), ferromagnetic damping alloys (Fe-Cr alloys), and multiphase damping alloys (Fe-Mn alloys). Damping alloys dominated by surface and line defects experience a decline in damping performance under long-term use or high-temperature operating conditions, with the disappearance of the damping source or the pinning and aggregation of point defects at the damping source. Furthermore, these alloys often sacrifice some mechanical properties to achieve excellent damping effects. Therefore, these alloys suffer from poor damping stability and low service temperature, and improvements in mechanical and damping properties are often mutually restrictive. In contrast, Snoek-type point defect damping alloys exhibit a thermally activated directional diffusion effect (i.e., Snoek relaxation effect) within a body-centered cubic matrix through interstitial atoms (C, O, N, etc.) under stress-induced stress, accompanied by energy consumption and damping effects. This diffusion effect is repeatable, does not alter the body-centered cubic structure of the matrix, and possesses high thermal stability. Therefore, this type of damping alloy offers advantages such as repeatability, strong thermal stability, high service temperature, wide application range, and long service life.
[0003] TiZr-based alloys possess advantages such as high strength, good ductility and toughness, low elastic modulus, and high O solid solubility. Therefore, TiZr alloys based on the Snoek-type relaxation effect of interstitial O atoms hold promise as a novel high-damping alloy material integrating structural and functional properties, possessing both excellent mechanical properties and high damping performance. High-entropy alloys, developed in recent years, have broken the constraints of traditional alloy design's single principal element approach. The novel concept of high-entropy alloying provides a broader compositional platform for alloy design and brings greater possibilities for the synergistic control of multiple alloy properties, offering new ideas for the integrated structural and functional design of alloys. However, for the design of high-damping TiZr alloys, the simple addition of Ti and Zr elements cannot form a stable single-phase BCC structure; further addition of BCC stabilizing elements such as Mo, Nb, Ta, and V is required for further stabilization. When multiple elements are mixed in equimolar proportions using the high-entropy alloying design concept, even with relatively weak inter-component interactions, a single-phase solid solution structure is easily formed. However, in some alloys, the separation of two BCC phases occurs, which impairs the alloy's mechanical and damping properties. For example, the yield strength of TiZrMoNbTa alloy is as high as σ. YSThe compressive strength is 1380 MPa, but due to the presence of a high-melting-point BCC1 phase rich in Mo / Nb / Ta and a low-melting-point BCC2 phase rich in Ti / Zr, its compressive plasticity is only δ = 4.6%. Furthermore, insufficient addition of BCC stabilizing elements leads to inadequate BCC stability and induces the precipitation of metastable phases (α′, α″, ω) in the BCC matrix, affecting the alloy's mechanical properties. In addition, oxygen (O), a key factor in high damping effect and a structural stabilizing element in BCC, can simultaneously improve the alloy's strength and plasticity. However, excessive O addition can also cause the precipitation of the ω phase in the matrix and promote the separation of the BCC phase, leading to a deterioration in the alloy's properties.
[0004] Therefore, in designing TiZr-based high-entropy alloys, the stability of the BCC structure and the precipitation behavior of the second phase are crucial to the mechanical and damping properties. It is necessary to rationally match the types and contents of each component to ensure the stability of the BCC structure and the precipitation of the second phase, and to control the amount of O added. In view of this, this invention employs the applicant's unique cluster-based composition design method, combined with the principle of high-entropy alloying. Through the rational addition of Ti, Zr, Nb, Ta, O, etc., a high-damping TiZr-based high-entropy alloy with both high strength and ductility over a wide temperature range and its preparation method are ultimately provided. By introducing interstitial O atoms, while ensuring high strength and ductility, the lattice distortion and hysteresis diffusion effects brought about by high-entropy alloying also result in high damping characteristics over a wide temperature range, making it a promising novel high-damping alloy material with integrated structural and functional properties. Summary of the Invention
[0005] This invention designs and develops a high-damping TiZr-based high-entropy alloy with both high strength and ductility over a wide temperature range, and its preparation method. The purpose of this invention is to address the current demand for structurally functionally integrated high-stability, high-damping performance, and excellent mechanical properties in damping alloys. Utilizing a cluster-based composition design method and the principle of high-entropy alloying, by introducing interstitial O atoms, a highly stable high-damping TiZr-based high-entropy alloy with both high strength and ductility over a wide temperature range is designed. This alloy is expected to become a high-damping alloy with integrated structural and functional properties suitable for high-temperature service environments.
[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0007] A high-damping TiZr-based high-entropy alloy exhibiting both high strength and ductility over a wide temperature range, comprising Ti, Zr, Hf, Nb, Ta, and O elements, is expressed as follows: (Ti a*(1-f) Zr b*(1-f) Hf c*(1-f) Nb d*(1-f) Ta e*(1-f) )O fWhere a = 16.67–22.22%, b = 44.44–61.1%, c = 0–22.22%, d = 5.56–16.67%, e = 0–11.11%, f = 1–1.8%, a + b + c + d + e = 100%; and d + e = 16.67%.
[0008] The high-damping TiZr-based high-entropy alloy has a unique microstructure: the alloy has a uniform BCC equiaxed matrix structure with a small amount of ω and α″ phases precipitated. Through the solid solution of O atoms in the interstitial spaces of the BCC lattice, a Snoek-type damping effect is generated, which simultaneously improves the strength and plasticity of the alloy.
[0009] Furthermore, the room temperature tensile yield strength σ of the aforementioned high-damping TiZr-based high-entropy alloy... YS >850MPa, tensile strength σ UTS >900MPa, tensile plasticity δ>10%; maximum damping value of the alloy in the frequency range of 1~4Hz. Peak temperature T P >700K, effective peak width ΔT>100K.
[0010] A method for preparing a high-damping TiZr-based high-entropy alloy with both high strength and ductility over a wide temperature range includes the following:
[0011] First, high-purity metal materials and TiO2 powder are used as raw materials and the ingredients are prepared according to the alloy composition. TiO2 is wrapped in pure Ti foil as an O additive and placed at the bottom of a Cu crucible. Then, other pure metal materials are added in sequence and melted at least 5 times in a vacuum electric arc furnace under Ar atmosphere protection to ensure uniform composition and obtain alloy ingots.
[0012] Next, the alloy ingot is placed in a quartz tube and vacuum-sealed. It is then homogenized by holding it at a specific temperature in a muffle furnace for a certain time. After removal, it is water-cooled and subsequently subjected to multiple cold rolling passes, with a total deformation of 85-95%, yielding a sheet with a thickness of 2-3 mm. The homogenization treatment temperature is 1223-1273 K, and the holding time is 2-3 hours.
[0013] Finally, the plate is placed in a quartz tube and vacuum-sealed. It is then subjected to solution treatment in a muffle furnace at a specific temperature for a certain time, followed by water cooling. The solution treatment temperature is 1223–1273 K, and the holding time is 0.5–1 hour.
[0014] The concept behind the above technical solution is to utilize the applicant's cluster composition design method to design the composition of high-damping TiZr-based high-entropy alloys. This composition design method is based on a "cluster + connecting atom" structural model, dividing the stable solid solution structure into two parts: clusters and connecting atoms. A cluster is a nearest-neighbor coordination polyhedron formed around a specific atom. For example, in the BCC structure, the cluster is a rhombic dodecahedron with a coordination number of 14, composed of 8 atoms in the nearest-neighbor shell and 6 atoms in the second-nearest-neighbor shell. This allows for the determination of a simple cluster composition formula: [cluster] (connecting atoms). X This means that a cluster is matched with a number of X connecting atoms. This cluster composition design method has been successfully applied to the composition design of alloys such as stainless steel, Ti alloys, Zr alloys, and high-entropy alloys, providing new ideas and methods for the composition design of high-performance engineering alloys.
[0015] For the Ti-Zr-Hf-Nb-Ta alloy system, we first consider that in the body-centered cubic structure, the nearest-neighbor cluster is a rhombic dodecahedron with a coordination number (CN) of 14. Ideally, the number of connecting atoms is calculated to be X=1 or X=3 under the guidance of Friedel's oscillation theory to stabilize the electronic structure. According to the cluster stacking model, for multi-component alloy systems containing elements with strong BCC stabilizing properties, the number of connecting atoms in the cluster formula is 1, such as the BCC structure Ti-Mo based alloys. Since the BCC structure stabilizing ability of Nb is not as strong as that of Mo, another BCC solid solution stable cluster formula needs to be selected, that is, containing 3 connecting atoms. This has been well confirmed in BCC-based multi-component Ti alloys. Therefore, we use the BCC (X=3) cluster connection model to design the composition of the Ti-Zr-Hf-Nb-Ta alloy. The positions of the alloying elements in the cluster composition were determined based on the strength of the interactions (mixing enthalpy) between the alloying elements, resulting in the basic cluster composition [Ti-(TiZrHf)] with a total of 18 atoms. 14[(NbTa)3.] For a simple TiZrHf ternary alloy system, it is difficult to form a stable BCC structure. Therefore, it is necessary to add BCC stabilizing elements such as Nb and Ta to further stabilize it. In previous work, we found that for the Zr-Nb-Ta alloy system, the lower limit of stability of Nb and Ta atoms is 3 / 18 = 16.67%. Excessive addition of Nb and Ta elements will lead to the precipitation of the ω phase or the separation of the BCC phase, which will seriously impair the mechanical and damping properties of the alloy. Subsequently, using the high-entropy alloying principle, we used Ti and Hf elements to replace Zr with similar elements to achieve a reasonable match of atomic additions and ensure the stability of the BCC phase structure. The content of Ti was limited to 3 / 18~4 / 18 = 16.67~22.22%, the content of Zr was limited to 8 / 18~11 / 18 = 44.44~61.1%, and the content of Hf was limited to 0~4 / 18 = 44.44~61.1%. For the addition of oxygen, we adopted an overall alloying approach, meaning that the proportion of each atom in the basic cluster structure was not changed. We controlled the oxygen content to be between 1% and 1.8%. Too low an oxygen content would result in insufficient improvement in the alloy's damping performance and strength-to-plasticity, while excessive oxygen content would lead to a large precipitation of the ω phase. Ultimately, we determined a high-damping TiZr-based high-entropy alloy with both high strength and plasticity over a wide temperature range, comprising Ti, Zr, Hf, Nb, Ta, and O. The atomic percentage (at.%) of its alloy composition is expressed as (Ti a*(1-f) Zr b*(1-f) Hf c*(1-f) Nb d*(1-f) Ta e*(1-f) )O f Where a = 16.67–22.22%, b = 44.44–61.1%, c = 0–22.22%, d = 5.56–16.67%, e = 0–11.11%, f = 1–1.8%, a + b + c + d + e = 100%; and d + e = 16.67%.
[0016] The preparation method of this invention is as follows: First, high-purity metal materials and TiO2 powder are used as raw materials, and the materials are prepared according to the alloy composition. TiO2, as an additive to O, is wrapped in pure Ti foil and placed at the bottom of a Cu crucible, followed by the addition of other pure metal materials. The alloy ingot is melted at least five times in a vacuum arc furnace under an Ar atmosphere to ensure uniform composition. Next, the alloy ingot is placed in a quartz tube and vacuum-sealed. It is then homogenized by holding at 1223K for 2 hours in a muffle furnace. After removal, it is water-cooled and then subjected to multiple cold rolling passes with a total deformation of approximately 90%, resulting in a sheet material with a thickness of approximately 2mm. Finally, the sheet material is placed in a quartz tube and vacuum-sealed. It is then solution-treated by holding at 1223K for 30 minutes in a muffle furnace. After removal, it is water-cooled.
[0017] The microstructure and structure of the alloy were examined using metallographic microscopy (OM), scanning electron microscopy (SEM), electron probe microanalysis (EPMA), transmission electron microscopy (TEM), and X-ray diffraction (XRD, Cu Kα radiation, λ = 0.15406 nm). Room temperature tensile properties were tested using a UTM5504 electronic universal tensile testing machine. The damping properties of the alloy in the 1–4 Hz frequency range were tested using a multi-functional internal friction analyzer (MFP-1000) under forced vibration mode. Based on this, the present invention is determined to be a high-damping TiZr-based high-entropy alloy possessing both high strength and ductility over a wide temperature range, comprising Ti, Zr, Hf, Nb, Ta, and O elements. The atomic percentage (at.%) of its alloy composition is expressed as (Ti a*(1-f) Zr b*(1-f) Hf c*(1-f) Nb d*(1-f) Ta e*(1-f) )O f Where a = 16.67–22.22%, b = 44.44–61.1%, c = 0–22.22%, d = 5.56–16.67%, e = 0–11.11%, f = 1–1.8%, a+b+c+d+e = 100%; and d+e = 16.67%. The typical performance indicators of the above high-damping TiZr-based high-entropy alloy are: room temperature tensile yield strength σ... YS >850MPa, tensile strength σ UTS >900MPa, tensile plasticity δ>10%; maximum damping value of the alloy in the frequency range of 1~4Hz. Peak temperature T P >700K, effective peak width ΔT>100K.
[0018] Compared with the prior art, the advantages of the present invention are as follows:
[0019] This invention presents a high-damping TiZr-based high-entropy alloy designed using our independently developed cluster composition method. This alloy exhibits both high strength and ductility over a wide temperature range. High-entropy alloying achieves a rational elemental ratio, ensuring the stability of the BCC structure. Interstitial solid solution of O atoms not only promotes dislocation cross-slip during deformation, enhancing the alloy's strength and ductility, but also induces a significant Snoek-type relaxation effect, resulting in high damping performance. Simultaneously, the lattice distortion effect brought about by high-entropy alloying raises the transition barrier of interstitial O atoms, resulting in a larger interstitial atom relaxation activation energy, thus increasing the damping peak temperature and effective peak width. Furthermore, the Snoek-type damping alloy exhibits higher thermal stability, improving its service life. This high-damping TiZr-based high-entropy alloy uses TiO2 powder as an O additive, simplifying the preparation process and significantly reducing material costs.
[0020] The effects and benefits of this invention are: ① Through intentional cluster-type composition design and high-entropy alloying, the addition amounts of each element are reasonably matched, thereby achieving a composite alloy with both wide-temperature-range high damping performance and excellent strength and plasticity, making it a structural and functional integrated material. ② The alloy melting and preparation process is simple and low-cost. ③ Through interstitial solid solution of O atoms, the resulting Snoek-type relaxation effect and the lattice distortion effect brought about by high-entropy alloying increase the relaxation activation energy and improve thermal stability, enabling the alloy to have high damping performance and a longer service life at higher temperatures, making it a promising damping structural material for use in high-temperature service environments. Attached Figure Description
[0021] Figure 1 Zr prepared in Example 1 43.64 Hf 21.82 Ti 16.37 Nb 16 .37O 1.8 OM microstructure of (at.%) alloy.
[0022] Figure 2 Zr prepared in Example 1 43.64 Hf 21.82 Ti 16.37 Nb 16.37 O 1.8 (at.%) TEM bright-field image of the alloy
[0023] Figure 3 Zr prepared in Example 1 43.64 Hf 21.82 Ti 16.37 Nb 16.37 O 1.8 Damping-temperature variation curves of (at.%) alloys.
[0024] Figure 4 Zr prepared in Example 2 44.00 Hf 22.00 Ti 16.50 Nb 16.50 O 1.0 (at.%) TEM bright-field image of the alloy
[0025] Figure 5 Zr prepared in Example 2 44.00 Hf 22.00 Ti 16.50 Nb 16.50 O 1.0 Damping-temperature variation curves of (at.%) alloys.
[0026] Figure 6 Zr prepared in Example 3 60.01 Ti 21.82Nb 5.46 Ta 10.91 O 1.8 SEM microstructure of the (at.%) alloy.
[0027] Figure 7 Zr prepared in Example 3 60.01 Ti 21.82 Nb 5.46 Ta 10.91 O 1.8 Damping-temperature variation curves of (at.%) alloys. Detailed Implementation
[0028] The specific embodiments of the present invention will be described in detail below with reference to the technical solution.
[0029] Example 1: Zr 43.64 Hf 21.82 Ti 16.37 Nb 16.37 O 1.8 (at.%) alloy
[0030] Step 1: Alloy Preparation
[0031] First, high-purity metal materials and TiO2 powder are used as raw materials, and the materials are prepared according to the alloy composition. TiO2, as an additive to O, is wrapped in pure Ti foil and placed at the bottom of a Cu crucible, followed by other pure metal materials. The alloy ingot is melted five times in a vacuum arc furnace under an Ar atmosphere to ensure uniform composition. Next, the alloy ingot is placed in a quartz tube and vacuum-sealed. It is then homogenized by holding at 1223K for 2 hours in a muffle furnace. After removal, it is water-cooled and then subjected to multiple cold rolling passes with a total deformation of 90%, resulting in a 3mm thick sheet. Finally, the sheet is placed in a quartz tube and vacuum-sealed. It is then solution-treated by holding at 1223K for 0.5 hours in a muffle furnace and water-cooled.
[0032] Step 2: Alloy microstructure and property testing
[0033] The microstructure of the alloy was examined using OM, SEM, EPMA, TEM, and XRD. The results showed that the alloy of this invention has a uniform BCC equiaxed matrix structure (see attached figure). Figure 1 A small amount of ω and α″ phases precipitated on the BCC matrix, see appendix. Figure 2 The room temperature tensile properties were tested using a UTM5504 electronic universal tensile testing machine, and the room temperature tensile yield strength σ was determined. YS =996MPa, tensile strength σ UTS=997MPa, tensile plasticity δ=15.1%; the damping performance of the alloy in the frequency range of 1-4Hz was tested using a multi-functional internal friction analyzer (MFP-1000) under forced vibration mode: the maximum damping value of the alloy in the frequency range of 1-4Hz was... Peak temperature T P =709K (0.5Hz), T P =723K (1Hz), T P =739K (2Hz), T P =752K (4Hz), effective peak width ΔT = 151K (0.5Hz), ΔT = 134K (1Hz), ΔT = 127K (2Hz), ΔT = 125K (4Hz), see appendix Figure 3 .
[0034] Example 2: Zr 44.00 Hf 22.00 Ti 16.50 Nb 16.50 O 1.0 (at.%) alloy
[0035] Step 1: Alloy Preparation
[0036] First, high-purity metal materials and TiO2 powder were used as raw materials, and the mixture was prepared according to the alloy composition. TiO2, as an additive to oxygen, was wrapped in pure Ti foil and placed at the bottom of a Cu crucible, followed by the addition of other pure metal materials. The mixture was melted six times in a vacuum arc furnace under an Ar atmosphere to ensure uniform composition, yielding an alloy ingot. Next, the alloy ingot was placed in a quartz tube and vacuum-sealed. It was then homogenized by holding at 1273K for 3 hours in a muffle furnace. After removal, it was water-cooled and subsequently subjected to multiple cold rolling passes, with a total deformation of 93%, resulting in a 2.5mm thick sheet. Finally, the sheet was placed in a quartz tube and vacuum-sealed. It was then solution-treated by holding at 1273K for 1 hour in a muffle furnace, and finally water-cooled.
[0037] Step 2: Alloy microstructure and property testing
[0038] The microstructure of the alloy was examined using OM, SEM, EPMA, TEM, and XRD. The results showed that the alloy of this invention has a uniform BCC equiaxed matrix structure; a small amount of ω phase precipitates are present on the BCC matrix (see attached figure). Figure 4 The room temperature tensile properties were tested using a UTM5504 electronic universal tensile testing machine, and the room temperature tensile yield strength σ was determined. YS =996MPa, tensile strength σ UTS=997MPa, tensile plasticity δ=15.1%; the damping performance of the alloy in the frequency range of 1-4Hz was tested using a multi-functional internal friction analyzer (MFP-1000) under forced vibration mode: the maximum damping value of the alloy in the frequency range of 1-4Hz was... Peak temperature T P =712K (0.5Hz), T P =723K (1Hz), T P =736K (2Hz), T P =752K (4Hz), effective peak width ΔT = 122K (0.5Hz), ΔT = 114K (1Hz), ΔT = 111K (2Hz), ΔT = 100K (4Hz), see appendix. Figure 5 .
[0039] Example 3: Zr 60.01 Ti 21.82 Nb 5.46 Ta 10.91 O 1.8 alloy
[0040] Step 1: Alloy Preparation
[0041] First, high-purity metal materials and TiO2 powder are used as raw materials, and the materials are prepared according to the alloy composition. TiO2, as an additive to O, is wrapped in pure Ti foil and placed at the bottom of a Cu crucible, followed by other pure metal materials. The alloy ingot is melted five times in a vacuum arc furnace under an Ar atmosphere to ensure uniform composition. Next, the alloy ingot is placed in a quartz tube and vacuum-sealed. It is then homogenized by holding at 1273K for 3 hours in a muffle furnace. After removal, it is water-cooled and then subjected to multiple cold rolling passes with a total deformation of 85%, resulting in a 3mm thick sheet. Finally, the sheet is placed in a quartz tube and vacuum-sealed. It is then solution-treated by holding at 1223K for 1 hour in a muffle furnace and water-cooled.
[0042] Step 2: Alloy microstructure and property testing
[0043] The microstructure of the alloy was examined using OM, SEM, EPMA, TEM, and XRD. The results showed that the alloy of the present invention has a uniform BCC equiaxed matrix structure; a small amount of BCC2 phase precipitates are present on the BCC matrix (see attached figure). Figure 6 The room temperature tensile properties were tested using a UTM5504 electronic universal tensile testing machine, and the room temperature tensile yield strength σ was determined. YS =990MPa, tensile strength σ UTS =1010MPa, tensile plasticity δ=11.6%; the damping performance of the alloy in the frequency range of 1-4Hz was tested using a multi-functional internal friction analyzer (MFP-1000) under forced vibration mode: the maximum damping value of the alloy in the frequency range of 1-4Hz was... Peak temperature T P =766K (0.5Hz), T P =762K (1Hz), T P =762K (2Hz), T P =753K (4Hz), effective peak width ΔT = 319K (0.5Hz), ΔT = 283K (1Hz), ΔT = 228K (2Hz), ΔT = 170K (4Hz), see appendix. Figure 7 .
[0044] Example 4: Zr 43.77 Hf 21.89 Ti 16.42 Nb 16.42 O 1.5 (at.%) alloy
[0045] Step 1: Alloy Preparation
[0046] First, high-purity metal materials and TiO2 powder were used as raw materials, and the mixture was prepared according to the alloy composition. TiO2, as an additive to O, was wrapped in pure Ti foil and placed at the bottom of a Cu crucible, followed by the addition of other pure metal materials. The mixture was melted five times in a vacuum arc furnace under an Ar atmosphere to ensure uniform composition, yielding an alloy ingot. Next, the alloy ingot was placed in a quartz tube and vacuum-sealed. It was then homogenized by holding at 1253K for 2.5 hours in a muffle furnace. After removal, it was water-cooled and subsequently subjected to multiple cold rolling passes, with a total deformation of 92%, resulting in a 2.8mm thick sheet. Finally, the sheet was placed in a quartz tube and vacuum-sealed. It was then solution-treated by holding at 1253K for 0.75 hours in a muffle furnace, and water-cooled after removal.
[0047] Step 2: Alloy microstructure and property testing
[0048] The microstructure of the alloy was examined using OM, SEM, EPMA, TEM, and XRD. The results showed that the alloy of this invention has a uniform BCC equiaxed matrix structure; a small amount of ω phase precipitates on the BCC matrix; the room temperature tensile properties were tested using a UTM5504 electronic universal tensile testing machine, and its room temperature tensile yield strength σ... YS =895MPa, tensile strength σ UTS =905MPa, tensile plasticity δ=10.6%; the damping performance of the alloy in the frequency range of 1-4Hz was tested using a multi-functional internal friction analyzer (MFP-1000) under forced vibration mode: the maximum damping value of the alloy in the frequency range of 1-4Hz was... Peak temperature T P =710K (0.5Hz), T P =720K (1Hz), T P =738K (2Hz), TP =751K (4Hz), effective peak width ΔT =135K (0.5Hz), ΔT =128K (1Hz), ΔT =124K (2Hz), ΔT =118K (4Hz).
[0049] The above-described embodiments are merely illustrative of the implementation methods of the present invention, but should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the protection scope of the present invention.
Claims
1. A high-damping TiZr-based high-entropy alloy possessing both high strength and ductility over a wide temperature range, characterized in that: The high-damping TiZr-based high-entropy alloy comprises Ti, Zr, Hf, Nb, Ta, and O elements, and its atomic percentage (at. %) is expressed as follows: Where a = 16.67~22.22%, b = 44.44~61.1%, c = 0~22.22%, d = 5.56~16.67%, e = 0~11.11%, f = 1~1.8%, a+b+c+d+e =100%; and d+e=16.67%; The high-damping TiZr-based high-entropy alloy possesses a unique microstructure: the alloy exhibits a uniform BCC equiaxed matrix structure with a small amount of ω and α´´ phases precipitated; Snoek-type damping effect is generated through the solid solution of O atoms in the BCC lattice interstices, simultaneously improving the alloy's strength and plasticity; the room temperature tensile yield strength of the high-damping TiZr-based high-entropy alloy is... σ YS >850 MPa, tensile strength σ UTS >900 MPa, tensile plasticity δ > 10%; in the frequency range of 1 ~ 4 Hz, the maximum damping value of the alloy (tan... ) max >0.016, peak temperature T P > 700 K, effective peak width ΔT > 100 K.
2. A method for preparing a high-damping TiZr-based high-entropy alloy with wide temperature range, high strength, and high plasticity as described in claim 1, characterized in that, Includes the following: First, high-purity metal materials and TiO2 powder are used as raw materials and are prepared according to the alloy composition. TiO2 is wrapped in pure Ti foil as an O additive and placed at the bottom of a Cu crucible. Then, other pure metal materials are added in sequence. The alloy ingot is obtained by melting multiple times in a vacuum arc furnace under Ar atmosphere protection to ensure uniform composition. Secondly, the alloy ingot is placed in a quartz tube and vacuum sealed. It is then placed in a muffle furnace for heat preservation and homogenization. After being taken out, it is water-cooled and then subjected to multiple cold rolling passes. The total deformation is 85-95% to obtain the sheet material. Finally, the plate was placed in a quartz tube and vacuum sealed. It was then placed in a muffle furnace for heat treatment and solution treatment. After removal, it was water-cooled to obtain the product.
3. The method for preparing a high-damping TiZr-based high-entropy alloy with wide temperature range, high strength, and high plasticity according to claim 2, characterized in that, The homogenization treatment temperature is 1223~1273K, and the holding time is 2~3h; the solution treatment temperature is 1223~1273K, and the holding time is 0.5~1h.
Citation Information
Patent Citations
Biomedical Ti-Zr-Hf-Nb-Ta series high-entropy alloy and preparing method
CN110423933A
Lightweight refractory multi-principal element alloy and preparation method and application thereof
CN115627406A